Acetylene reduction (dinitrogen fixation) and nitrification in soil as affected by the structural aggregate size - Skrdleta, V; Hyndráková, A; Nĕmocová, M (Folia microbiologica, 1979)
The effect of size of structural aggregates on the intensity of nitrification and nitrogenase (nitrogen: acetylene oxidoreductase) activity was investigated in three soils. In two of them the nitrogenase activity was limited by addition of glucose. Aggregates of a larger diameter (2-4 mm) exhibited a considerably higher nitrogenase activity than those with a diameter smaller than 2 mm. This effect was even more pronounced when the soil samples were repeatedly intensively aerated. On the contrary, smaller aggregates (0.5-2 mm) exhibited more intensive nitrification.
Keywords: acetylen; nitrogenasa; velikost částic; Nitrates; Acetylene; Nitrogen Fixation; oxidace-redukce; Soil Microbiology; Soil; půdní mikrobiologie; Nitrogenase; Oxidation-Reduction; Bacteria; dusičnany; půda; Particle Size; fixace dusíku